Saponins from Sanguisorba officinalis Improve Hematopoiesis by Promoting Survival through FAK and Erk1/2 Activation and Modulating Cytokine Production in Bone Marrow - Chen, Xin; Li, Bogang; Gao, Yue; Ji, Jianxin; Wu, Zhongliu; Chen, Shuang (Frontiers in Pharmacology, 2017)
Radix Sanguisorbae, the root of Sanguisorba officinalis L. is used as traditional Chinese medicine. In recent decades it has been reported to be clinically effective against myelosuppression induced by chemotherapy and/ or radiotherapy. However, the underlining mechanism has not been well studied. In this work, we evaluated the hematopoietic effect of total saponins from S. officinalis L. on myelosuppressive mice induced by cyclophosphamide and by 60Co-γ-irradiation and confirmed the therapeutic effect. Then, we found total saponins and their characteristic constituents Ziyuglycoside I and ziyuglycoside II can inhibit apoptosis of TF-1 cells caused by cytokine deprivation, and promote survival of mouse bone marrow nuclear cells through focal adhesion kinase (FAK) and extracellular signal-regulated kinase 1/2 (Erk1/2) activation in vitro. In addition, they can down-regulate macrophage inflammatory protein 2 (MIP-2), platelet factor 4 (PF4) and P-selectin secretion, which are reported to be suppressive to hematopoiesis, both in vitro and in vivo. These results suggest that promotion of survival through FAK and Erk1/2 activation and inhibition of suppressive cytokines in the bone marrow is likely to be the pharmacological mechanism underlying the hematopoietic effect of saponins from S. officinalis L.